PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII3 SMP NEGERI 32 PEKANBARU TAHUN PELAJARAN 2011/2012 - Rosmaini S; Darmawati '; Ria Puspita Sari (Biogenesis, 2011)
Classroom Action Research has been conducted on the implementation of cooperative learning model of type Time Token to enhance the activity and student learning outcomes Biology class 32 Pekanbaru VIII3 SMP 2011/2012 school year from July to September 2011. Student activity is an activity or behavior that occur during the learning process which is one indicator of the desire of students to learn. Learning outcomes is the embodiment of the values obtained students through the learning process. Research subjects were 32 students in grade VIII3 SMP Pekanbaru, amounting to 36 students, consisting of 21 male students and 15 female students. The parameters of this study is student activity and learning outcomes. Average student activity increasedat each cycle, the cycle I pretty category (76.6%) whereas in the second cycle category of both (83.84%). Average student activity also increased in each indicator is the indicator to readtextbooks, answer questions, provide feedback, and conduct discussions. The average increase student learning outcomes, this can be seen from the results of absorption and completeness of individual student learning. Absorptive capacity of students was increasing at eachcycle, the cycle I pretty category (75.41%) while in the second cycle of either category (80.27%). Award at the group I with predicate super cycle is obtained in group I, while in the secondcycle with the predicate obtained super group III. From the research results can be concluded that with the implementation of cooperative learning model of type Time Token can increase the activity and learning outcomes VIII3 grade Biology students SMPN 32 Pekanbaru.Keywords: Cooperative Learning Model Time Token Type, Learning Activities and Learning Outcomes